1999
DOI: 10.4141/p98-079
|View full text |Cite
|
Sign up to set email alerts
|

Yield and injury effects on vegetable crops planted in flumetsulam-treated soil

Abstract: . 1999. Yield and injury effects on vegetable crops planted in flumetsulam-treated soil. Can. J. Plant Sci. 79: 417-420. The effect of flumetsulam on several vegetable crops grown following soybean was investigated over a 4-yr period. Flumetsulam was applied preplant incorporated to soybean at 0, 70 and 140 g a.i. ha -1 from 1992 to 1994. In trials 1 yr after flumetsulam application, cabbage (Brassica oleracea var. capitata), potato (Solanum tuberosum L.), tomato (Lycopersicon esculentum L.), and pepper (Capsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…At 70 DAT, plant height was measured, and above-and belowground biomasses were harvested. Plant material was dried for 7 d at 70 C. Although the presented research did not collect crop yield data, previous reports have shown yield data responds similarly with the evaluated parameters (Everitt and Keeling 2009;O'Sullivan et al 1999;Pfleeger et al 2011). Plant harvest data were converted to percent reduction relative to the nontreated within a replicate using the equation…”
Section: Methodsmentioning
confidence: 99%
“…At 70 DAT, plant height was measured, and above-and belowground biomasses were harvested. Plant material was dried for 7 d at 70 C. Although the presented research did not collect crop yield data, previous reports have shown yield data responds similarly with the evaluated parameters (Everitt and Keeling 2009;O'Sullivan et al 1999;Pfleeger et al 2011). Plant harvest data were converted to percent reduction relative to the nontreated within a replicate using the equation…”
Section: Methodsmentioning
confidence: 99%
“…Flumetsulam is a sulfonanilide herbicide which inhibits the Acetolactate Synthase enzyme (ALS) and in particular, the formation of the amino acids valine, leucine and isoleucine. This herbicide was expected to show phytotoxicity in Tobacco as broadleaf crops are known to be sensitive (O'Sullivan, Thomas & Bouw 1999) even to carry over residues (Noy & Hollaway 1999). Dual Magnum (Metolachlor), 2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl) acetamide, inhibits the biosynthesis of very long chain fatty acids.…”
Section: Introductionmentioning
confidence: 99%